Hubungan Jarak Tempuh Dengan Frekuensi Kunjungan Ke Puskesmas Bontonompo II Tahun 2025 - Nurfalia Harfah; Salwah Suardi; Titim Sri Melyana; Hendrayadi Hendrayadi (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
The Community Health Center (Puskesmas) serves as a primary healthcare facility that plays a vital role in providing essential health services to the community. However, the frequency of community visits to puskesmas remains varied, and one of the influencing factors is the distance between residence and the healthcare facility. This study aims to determine the relationship between travel distance and the frequency of visits to the puskesmas. This research employed a quantitative method with a correlational analytic design (cross-sectional study). The study was conducted at Bontonompo II involving 90 respondents selected through accidental sampling technique. Data were collected using a structured questionnaire and distance observation. The data were analyzed using univariate analysis to describe respondents’ characteristics and bivariate analysis with the Spearman Rank test at a 0.05 significance level. Statistical test results show a significant relationship between distance traveled and the frequency of visits to community health centers (p < 0.001), with a negative relationship, meaning the longer the distance traveled, the lower the frequency of visits. In conclusion, distance traveled influences the level of utilization of health services at community health centers.